Regulation of anti-phage defense mechanisms by using cinnamaldehyde as a quorum sensing inhibitor - Barrio-Pujante, Antonio; Bleriot, Inés; Blasco, Lucía; Fernández-Garcia, Laura; Pacios, Olga; Ortiz-Cartagena, Concha; Cuenca, Felipe Fernández; Oteo-Iglesias, Jesús; Tomás, María (Frontiers in Microbiology, 2024)
Background Multidrug-resistant bacteria and the shortage of new antibiotics constitute a serious health problem. This problem has led to increased interest in the use of bacteriophages, which have great potential as antimicrobial agents but also carry the risk of inducing resistance. The objective of the present study was to minimize the development of phage resistance in Klebsiella pneumoniae strains by inhibiting quorum sensing (QS) and thus demonstrate the role of QS in regulating defense mechanisms. Results Cinnamaldehyde (CAD) was added to K. pneumoniae cultures to inhibit QS and thus demonstrate the role of the signaling system in regulating the anti-phage defense mechanism. The QS inhibitory activity of CAD in K. pneumoniae was confirmed by a reduction in the quantitative expression of the lsrB gene (AI-2 pathway) and by proteomic analysis. The infection assays showed that the phage was able to infect a previously resistant K. pneumoniae strain in the cultures to which CAD was added. The results were confirmed using proteomic analysis. Thus, anti-phage defense-related proteins from different systems, such as cyclic oligonucleotide-based bacterial anti-phage signaling systems (CBASS), restriction–modification (R–M) systems, clustered regularly interspaced short palindromic repeat-Cas (CRISPR-Cas) system, and bacteriophage control infection (BCI), were present in the cultures with phage but not in the cultures with phage and CAD. When the QS and anti-phage defense systems were inhibited by the combined treatment, proteins related to phage infection and proliferation, such as the tail fiber protein, the cell division protein DamX, and the outer membrane channel protein TolC, were detected. Conclusion Inhibition of QS reduces phage resistance in K. pneumoniae, resulting in the infection of a previously resistant strain by phage, with a significant increase in phage proliferation and a significant reduction in bacterial growth. QS inhibitors could be considered for therapeutic application by including them in phage cocktails or in phage-antibiotic combinations to enhance synergistic effects and reduce the emergence of antimicrobial resistance.